Emergence of the novel sixth Candida auris Clade VI in Bangladesh - Tahsin Khan; Naimul Islam Faysal; Md Mobarok Hossain; Syeda Mah-E-Muneer; Arefeen Haider; Shovan Basak Moon; Debashis Sen; Dilruba Ahmed; Lindsay A. Parnell; Mohammad Jubair; Nancy A. Chow; Fahmida Chowdhury; et al. (Microbiology Spectrum, 2024)
ABSTRACT Candida auris, initially identified in 2009, has rapidly become a critical concern due to its antifungal resistance and significant mortality rates in healthcare-associated outbreaks. To date, whole-genome sequencing (WGS) has identified five unique clades of C. auris, with some strains displaying resistance to all primary antifungal drug classes. In this study, we presented the first WGS analysis of C. auris from Bangladesh, describing its origins, transmission dynamics, and antifungal susceptibility testing (AFST) profile. Ten C. auris isolates collected from hospital settings in Bangladesh were initially identified by CHROMagar Candida Plus, followed by VITEK2 system, and later sequenced using Illumina NextSeq 550 system. Reference-based phylogenetic analysis and variant calling pipelines were used to classify the isolates in different clades. All isolates aligned ~90% with the Clade I C. auris B11205 reference genome. Of the 10 isolates, 8 were clustered with Clade I isolates, highlighting a South Asian lineage prevalent in Bangladesh. Remarkably, the remaining two isolates formed a distinct cluster, exhibiting >42,447 single-nucleotide polymorphism differences compared to their closest Clade IV counterparts. This significant variation corroborates the emergence of a sixth clade (Clade VI) of C. auris in Bangladesh, with potential for international transmission. AFST results showed that 80% of the C. auris isolates were resistant to fluconazole and voriconazole, whereas Clade VI isolates were susceptible to azoles, echinocandins, and pyrimidine analogue. Genomic sequencing revealed ERG11_Y132F mutation conferring azole resistance while FCY1_S70R mutation found inconsequential in describing 5-flucytosine resistance. Our study underscores the pressing need for comprehensive genomic surveillance in Bangladesh to better understand the emergence, transmission dynamics, and resistance profiles of C. auris infections. Unveiling the discovery of a sixth clade (Clade VI) accentuates the indispensable role of advanced sequencing methodologies.IMPORTANCECandida auris is a nosocomial fungal pathogen that is commonly misidentified as other Candida species. Since its emergence in 2009, this multidrug-resistant fungus has become one of the five urgent antimicrobial threats by 2019. Whole-genome sequencing (WGS) has proven to be the most accurate identification technique of C. auris which also played a crucial role in the initial discovery of this pathogen. WGS analysis of C. auris has revealed five distinct clades where isolates of each clade differ among themselves based on pathogenicity, colonization, infection mechanism, as well as other phenotypic characteristics. In Bangladesh, C. auris was first reported in 2019 from clinical samples of a large hospital in Dhaka city. To understand the origin, transmission dynamics, and antifungal-resistance profile of C. auris isolates circulating in Bangladesh, we conducted a WGS-based surveillance study on two of the largest hospital settings in Dhaka, Bangladesh.